Perceptuo-affective organization of touched materials in younger and older adults - Drewing, Knut; Justus Liebig University Giessen (My University, 2024)
In everyday interaction we touch different materials, which we experience along a limited number of perceptual and emotional dimensions: For instances, a furry surface feels soft and pleasant, whereas sandpaper feels rough and unpleasant. In a previous study, younger adults manually explored a representative set of solid, fluid and granular materials. Their ratings were made along six perceptual dimensions (roughness, fluidity, granularity, deformability, fibrousness, heaviness) and three emotional ones (valence, arousal, dominance). Perceptual and emotional dimensions were systematically correlated. Here, we wondered how this perceptuo-affective organization of touched materials depends on age, given that older adults show decline in haptic abilities, in particular detail perception. 30 younger participants (~22 years, half females) and 15 older participants (~66 years) explored 25 materials using 18 perceptual and 9 emotional adjectives. We extracted 6 perceptual and 2 emotional dimensions. Older and younger adults showed similar dimensions. However, in younger participants roughness and granularity judgments were done separately, while they were collapsed in a single dimension in older people. Further, age groups differed in the perception of roughness, granularity and valence, and older people did not show a positive correlation between valence and granularity as did younger people. As expected, control analyses between young males and females did not reveal similar gender differences. Overall, the results demonstrate that older people organize and experience materials partly differently from younger people, which we lead back to sensory decline. However, other aspects of perceptual organization that also include fine perception are preserved into older age.
Keywords: ddc:150